2012
DOI: 10.1002/jbm.a.34100
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin interactions with immobilized anti‐hCG studied by quartz‐crystal microbalance with dissipation monitoring

Abstract: Previous studies have found that commercial human pregnancy tests are often too insensitive to function to their advertised >99% accuracy. Improper orientation of proteins used for recognition of ligands in sensors can often prevent the binding site from being available to the ligand, thereby decreasing sensor sensitivity. We have developed a simple method for the immobilization of anti‐human chorionic gonadotropin on a sensor surface that maximizes its sensitivity by ensuring ligand binding sites are exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The detected amount of hIgG by the anti-human biointerface and oriented anti-human biointerface (0.90 ± 0.09 and 1.28 ± 0.11 mg/m 2 , respectively) with D 33 - b -EGMA 137 passivation (Figures a and ) was good compared to other reported anti-human IgG biointerfaces based on cellulose , and to other hIgG binding surfaces ,, prepared on alkanethiol self-assembled monolayers and grafted copolymer brush surfaces. The results for adsorbed amount of hIgG and anti-hIgG are also comparable to those reported for other antibodies. , This clearly demonstrates that while the block copolymers provide the biointerface with much-needed surface passivation to avoid false responses, the functionality of the biointreface is not compromised or reduced by their use. Furthermore, as interest in utilization of cellulose-based products in biomedical applications increases it is important to understand their interactions with biomolecules, the only way to control and tailor the systems to the specific needs.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The detected amount of hIgG by the anti-human biointerface and oriented anti-human biointerface (0.90 ± 0.09 and 1.28 ± 0.11 mg/m 2 , respectively) with D 33 - b -EGMA 137 passivation (Figures a and ) was good compared to other reported anti-human IgG biointerfaces based on cellulose , and to other hIgG binding surfaces ,, prepared on alkanethiol self-assembled monolayers and grafted copolymer brush surfaces. The results for adsorbed amount of hIgG and anti-hIgG are also comparable to those reported for other antibodies. , This clearly demonstrates that while the block copolymers provide the biointerface with much-needed surface passivation to avoid false responses, the functionality of the biointreface is not compromised or reduced by their use. Furthermore, as interest in utilization of cellulose-based products in biomedical applications increases it is important to understand their interactions with biomolecules, the only way to control and tailor the systems to the specific needs.…”
Section: Resultssupporting
confidence: 79%
“…The results for adsorbed amount of hIgG and anti-hIgG are also comparable to those reported for other antibodies. 54,55 This clearly demonstrates that while the block copolymers provide the biointerface with much-needed surface passivation to avoid false responses, the functionality of the biointreface is not compromised or reduced by their use. Furthermore, as interest in utilization of cellulose-based products in biomedical applications increases it is important to understand their interactions with biomolecules, the only way to control and tailor the systems to the specific needs.…”
Section: ■ Experimental Sectionmentioning
confidence: 89%
“…Nevertheless, in the patient with the trophoblastic tumor, the hCG secretion can increase up to 10,000 mIU/mL at 5 weeks, 1000 mIU/mL at 8 weeks, or detectable at 24 weeks after the evacuation of the mole, at which point is recommended for the patient to undergo chemotherapy [133,135]. Several studies reported the detection of hCG in biosensor platforms, such as in magnetometer-based biosensor [8,[136][137][138], plasmonic-based biosensor [139,140], QCM platform [141], and FET-based device [142].…”
Section: Single Biomarkermentioning
confidence: 99%
“…Nevertheless, in the patient with the trophoblastic tumor, the hCG secretion can increase up to 10,000 mIU/mL at 5 weeks, 1000 mIU/mL at 8 weeks, or detectable at 24 weeks after the evacuation of the mole, at which point is recommended for the patient to undergo chemotherapy [136,137]. Several studies reported the detection of hCG in biosensor platforms, such as in magnetometer-based biosensor [8,[138][139][140], plasmonic-based biosensor [141,142], QCM platform [143],…”
Section: Single Biomarkermentioning
confidence: 99%